The effects of mutating the CD loops of TgCIA1 on mitochondrial morphology and parasite proliferation. - Evie R. Hodgson (21866946) (2025)
(A) Relative abundances of proteins depicted in the Fig 6B western blots were determined as a percentage of the -IAA condition for the cTgCIA1WT-Ty1 protein and normalized using the TgTom40 loading control. Data points represent the mean ± SD of three independent experiments. Data were analyzed using a one-way ANOVA followed by Tukey’s multiple comparisons test, with significant p values (<0.05) with respect to the -IAA condition of the cTgCIA1WT-Ty1-IAA protein shown. (B) Quantification of mitochondrial morphology in rTgCIA1-mAID-HA/cTgCIA1WT-Ty1 (WT-Ty1), rTgCIA1-mAID-HA/cTgCIA1ScCD1-Ty1 (ScCD1-Ty1), rTgCIA1-mAID-HA/cTgCIA1ScCD3-Ty1 (ScCD3-Ty1), and rTgCIA1-mAID-HA/cTgCIA1ScCD5-Ty1 (ScCD5-Ty1) parasites. Mitochondria were observed by immunofluorescence assays using anti-TgTom40 antibodies, and were classified as lasso, branched, linear, or tadpole shaped, with representative images of each category shown above. The morphologies of mitochondria in 150 vacuoles containing 4–16 intracellular parasites were determined in each parasite line across three independent experiments, with the observer blinded to the identities of the samples being examined. (C–E) Plaque assays of rTgCIA1-mAID-HA parasites and rTgCIA1-mAID-HA parasites constitutively expressing TgCIA1 variants, including (C) cTgCIA1WT-Ty1 (WT-Ty1), cTgCIA1ScCD1-Ty1 (ScCD1-Ty1), cTgCIA1ScCD3-Ty1 (ScCD3-Ty1) and cTgCIA1ScCD5-Ty1 (ScCD5-Ty1), (D) cTgCIA1WT-Ty1 (WT-Ty1), cTgCIA1CD5-to-CD1-Ty1 (CD5-to-CD1-Ty1), cTgCIA1VbCD5-Ty1 (VbCD5-Ty1), and cTgCIA1SmCD5-Ty1 (SmCD5-Ty1), and (E) cTgCIA1WT-Ty1 (WT-Ty1), cTgCIA1W526A-Ty1 (W526A-Ty1) cTgCIA1Y527A-Ty1 (Y527A-Ty1), cTgCIA1F532A-Ty1 (F532A-Ty1), and cTgCIA1R533A-Ty1 (R533A). Parasites were cultured in the absence (top) or presence (bottom) of IAA for six days and are representative of three independent experiments. Each plaque assay was set up simultaneously with the fluorescence proliferation assays depicted in Figs 6F, 7C, 8I, 9D, and S12G. The numerical data underlying this Figure can be found in S1 Data. (TIF)